SINERGITAS PERAN KPK DAN MASYARAKAT DALAM MENCEGAH TINDAK PIDANA KORUPSI DANA BANTUAN SOSIAL COVID-19: SINERGITAS PERAN KPK DAN MASYARAKAT DALAM MENCEGAH TINDAK PIDANA KORUPSI DANA BANTUAN SOSIAL COVID-19 - Nurul Husna, Yonimah; Lailiyah, Kusroh; Kurniawan, Devi Dwi (Badan Pemeriksa Keuangan Republik Indonesia, 2021)
This study aims to unearth the corrupt practices that occur in the delivery of COVID-19’s social assistance and discover the actions undertaken by KPK and the community in preventing the corruption of COVID-19 social assistance funds. The method used in this study is normative juridical with a statutory study approach and case studies. The method used is a literature study and analyzed using qualitative descriptive. The results of this study indicate that there have been several fraud cases, including corruption of the COVID-19 social assistance. The role of the community in efforts to prevent corruption of the COVID-19 social assistance fund is to supervise and report any irregularities. Meanwhile, the role of KPK is to conduct a whistleblowing system to prevent corruption of COVID-19 social assistance funds. With this research in place, it is expected to optimize the role of the Corruption Eradication Commission and the community in preventing corruption.